2020
DOI: 10.1186/s12891-020-03452-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphosphonates or teriparatide on mechanical complications after posterior instrumented fusion for osteoporotic vertebral fracture: a multi-center retrospective study

Abstract: Background: The optimal treatment of osteoporosis after reconstruction surgery for osteoporotic vertebral fractures (OVF) remains unclear. In this multicentre retrospective study, we investigated the effects of typically used agents for osteoporosis, namely, bisphosphonates (BP) and teriparatide (TP), on surgical results in patients with osteoporotic vertebral fractures. Methods: Retrospectively registered data were collected from 27 universities and affiliated hospitals in Japan. We compared the effects of BP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…A retrospective comparative study with bisphosphonate showed a significantly higher union rate at 6 months in the teriparatide group and suggested that teriparatide could enhance fracture healing in OVCF [86]. Teriparatide also showed bet-ter results than bisphosphonate in preventing mechanical complications after posterior instrumented fusion for OVF [87].…”
Section: Medical Management Of Fracture Healingmentioning
confidence: 99%
“…A retrospective comparative study with bisphosphonate showed a significantly higher union rate at 6 months in the teriparatide group and suggested that teriparatide could enhance fracture healing in OVCF [86]. Teriparatide also showed bet-ter results than bisphosphonate in preventing mechanical complications after posterior instrumented fusion for OVF [87].…”
Section: Medical Management Of Fracture Healingmentioning
confidence: 99%
“…However, there was no difference in screw loosening, subsequent vertebral fracture, VAS, or ODI. 38 Such findings heavily affected the preferred therapy algorithm, especially when bisphosphonates, including ZOL, are still the first-line choice. However, the detailed instructions and practical application of TPTD vary from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, poor bone health commonly manifests as osteoporosis,41,42 malnutrition, or obesity 43. Teriparatide use has been shown to decrease rates of pseudarthrosis in patients with osteoporosis, though this study was in vertebral fractures of all levels 41. Third, an inability to mount an adequate inflammatory response has also been cited in rheumatologic conditions requiring chronic steroid use 44.…”
Section: Methodsmentioning
confidence: 99%